Daddy putdown. - Penguin Young Readers Group (Penguin Young Readers Licenses, an imprint of Penguin Random House LLC, 2024)
Charged with taking care of Bluey and Bingo for the night, Dad embarks on a mission to keep her entertained when Bluey starts missing Mum.
When Mum goes to a baby shower, Dad is in charge of taking care of Bluey and Bingo for the night. When Bluey misses Mum, he has to find a way to keep her entertained! Can Dad distract Bluey?
At head of title: Bluey.
"This book is based on the TV series Bluey"--Title page verso.
AD510L
Decoding demand: 71 (high) Semantic demand: 67 (high) Syntactic demand: 77 (high) Structure demand: 82 (very high)
Keywords: Bluey -- (Fictitious character) -- Juvenile fiction; Australian cattle dog -- Juvenile fiction; Dogs -- Juvenile fiction; Play -- Juvenile fiction; Families -- Juvenile fiction; Showers (Parties) -- Juvenile fiction; Bedtime -- Juvenile fiction; Picture books